PERSIJAP JEPARA MENGARUNGI LIGA 2 2021 PADA MASA PANDEMI COVID 19 DALAM FOTOGRAFI DOKUMENTER - Prasetyo, Ahmad Nur; Saryana, I Made; Candrayana, Ida Bagus (Lp2mpp Isi Denpasar - Ps. Fotografi, 2022)
Jepara city is one of the cities at the tip of Java Island. In addition, this district is also known as a wood carving craft producing area that is famous to foreign countries, in 1954 The Regent of Jepara Sahlan Ridwan wanted to form a team owned by Jepara Regency. This idea is based on the growing number of clubs. That year was then recorded as the year of the founding of Persijap Jepara precisely on April 11, 1954. Persijap Jepara has the nickname Laskar Kalinyamat and has supporters banaspati, Jetman and CNS. Persijap is in League 2 for 2021. Liga 2 Indonesia finally resumed in 2021 by implementing health protocols provided by the government, Liga 2 stopped in 2020 due to the spread of the Corona virus. The creator uses the method of observation and literature study in the creation of this work and performs the shooting process then selected the best photo and editing process, after that to the final stage of exhibition and presentation of the work. In this work the creator raised a documentary photo To visualize the final task work